Investigations of paleogeographic variations on the basis of the stratotype section of Viatovo at the Lower Danube - Kis, Éva; Schweitzer, Ferenc; Palcsu, László; Futó, István; Balogh, János; Di Gléria, Mária (Hungarian Geographical Bulletin, 2012)
The Plio-Pleistocene changes of paleogeographic environment in the Lower Danube Basin were investigated with the involvement of new granulometric analytical methods. The loess-paleosol series at Viatovo (located 35 km to the SE from Russe, Bulgaria) provides a comprehensive archive of Pleistocene climate changes. Similarly to Moravian loess deposits, the investigated site situates in a corridor position between more glaciated terrains. The completeness of horizontally-bedded loess and paleosoil layers makes it a particularly significant section in Central and Eastern Europe. With or new data, we would like to contribute to previous lithological, paleoenvironmental and chronological studies of the section.The novelty in our study are the comparison and plotting of δ18O values and our newly introduced indices (fineness grade: Fg and degree of weathering: Kd) together with traditional sedimentary parameters (Md, So, K, Sk). These values were competed with clay- and CaCO3-content, and percentages of clay, silt, loess and sand. To the relative dating of the section, we have correlated our data with Marine Isotope Stages of the ODP-677 site. The series of the upper part of the section represent 100 ky cycles of Middle and Late Pleistocene climate changes.These units are overlying the ca. 6 m thick red clay deposits and the lowermost sandy kaolinitic loess layer. The whole sequence is situated on Lower Cretaceous paleokarst system. The δ18O values and other sedimentary parameters illustrate gradual decrease of temperature since the Pliocene. The granulometric parameters suggest that pedogenic processes played also a dominant role during the formation of loess deposits. The clay and fine-silt content of the red clay, loess and paleosoil layers are also in the range of 65–90%. These loess deposits can be classified as “Mediterranean” loess. An identified horizon with clay fragments in the upper part of the loess-paleosoil series can be employed as marker unit, and supports the correlation with other sections.The lower 3 paleosoils were formed under moister climate regimes, the more infiltered precipitation washed out the carbonates from these layers. The formation and evolution of river-terraces, denudation surfaces and valleys can also be observed well in the vicinity of the section.